The sustainable development: ethical considerations. - Tortoreto, D.; Sgreccia, E. (Medicina e Morale, 2003)
With reference to current trends of international policies, the sustainable development provides the programme of action to eradicate poverty, protect human health, safeguard the environment. The fundamental principle for achieving a sustainable development is the dignity of human person. In this regard, the World Summit on Sustainable Development adopted a pratical and visible plan to build a humane, equitable and caring global society. The sustainable development gives priority to human health. There is an urgent need to develop or streghthen programmes to address the cause of illness, including environmental causes, and in particular to promote access to medicines for all. The Summit in Johannesburg also confirmed the efforts to respond to the problem of environmental degradation through improving eco-efficency, supporting cleaner production programmes, and encouraging the diffusion of environmental technologies in all countries. The realization of the three components of sustainable development, development economic, social development and environmental safeguard, can be achieved only throught increasing population. Finally, to reverse the "ideological" interpretation of sustainable development, it is necessary to acknowledge the importance of ethics for sustainable development focused on the dignity of human person.